Approaches to the aesthetic-literary thought of Felipe Buendía in his surrealist fantasy narrative - Rojas Vargas, Abraham Eduardo (2023)
The purpose of this article is to bring the reader closer to the aesthetic-literary thought of the writer Felipe Buendía (1927-2002) concerning his surrealist fantastic narrative. To this end, it briefly reviews his artistic trajectory as a born creator by reproducing fragments of interviews; and, in addition, it studies his link with the 50’s generation and the literary influences of the time. Buendía is an author very little approached by literary critics and his work has not been widely disseminated, except for his famous story «El baúl», a classic work of the Peruvian fantastic narrative reviewed and included in several anthologies. In this paper, we will approach this narrative, which is conceived under a vital, experiential, metaphysical and, at the same time, critical poetics of reality, in addition to the prominence of the fantastic and literary surrealism.